The Bochner integral for measurable sections and its properties - Ganiev, Inomjon; Mahmoud Ahmed, Gharib Subhi (2013)
In the present paper we introduce the notion Bochner integral for measurable sections and study some properties such integrals. Given necessary and successfully condition for integrability of a measurable section. Dominated convergence theorem and analogue of Hille's theorem are proved.